Blood Culture-Negative but Clinically Diagnosed Infective Endocarditis Complicated by Intracranial Mycotic Aneurysm, Brain Abscess, and Posterior Tibial Artery Pseudoaneurysm. (8th November 2018) - Jiang, Chao; Lu, Haibin; Guo, Yaoqiang; Zhu, Li; Luo, Tianqi; Ziai, Wendy; Wang, Jian
Abstract : Blood culture-negative endocarditis is often severe and difficult to diagnose. It is necessary to emphasize the importance for the early diagnosis and accurate treatment of blood culture-negative endocarditis. Here, we described the relevant clinical information of a blood culture-negative but clinically diagnosed infective endocarditis complicated by intracranial mycotic aneurysm, brain abscess, and posterior tibial artery pseudoaneurysm. This patient was a 65-year-old man with a 9-month history of intermittent fever and died in the end for the progressive neurological deterioration. Although the blood culture is negative, this patient was clinically diagnosed as infective endocarditis according to Duke criteria. This patient course was complicated not only by cerebral embolism, intracranial mycotic aneurysm, and brain abscess but also by posterior tibial artery aneurysm of the lower extremity. The clinical findings of this patient suggest that the confirmatory microbiology is essential for the treatment of blood culture-negative infective endocarditis. Clinicians should be aware of the detriment of blood culture-negative infective endocarditis for its multiple complications may occur in one patient. The delayed etiological diagnosis and insufficient treatment may aggregate the clinical outcome of blood culture-negative infective endocarditis.